Scalar field description of decaying-[Formula Presented] cosmologies - Maia, J. M.F. [UNESP]; Lima, J. A.S. [UNESP] (American Physical Society (APS), 2002)
The conditions under which cosmologies driven by time-varying cosmological terms can be described by a scalar field coupled to a perfect fluid are discussed. An algorithm to reconstruct potentials dynamically and thermodynamically analogous to given phenomenological (Formula presented) models is presented. As a working example, the deflationary cosmology which evolves from a pure de Sitter vacuum state to a slightly modified Friedmann-Robertson-Walker cosmology is considered. It is found that this is an example of nonsingular warm inflation with an asymptotic exponential potential. Differences with respect to other scalar field descriptions of decaying vacuum cosmologies are addressed and possible extensions are indicated. © 2002 The American Physical Society.